Chemical analysis of Karenia papilionacea. (July 2015) - Fowler, Nicholas; Tomas, Carmelo; Baden, Daniel; Campbell, Lisa; Bourdelais, Andrea
Abstract: One of the most widely studied organisms responsible for Harmful Algal Blooms (HABs) is the marine dinoflagellate Karenia brevis . This organism produces neurotoxic compounds known as brevetoxins. A related dinoflagellate, Karenia papilionacea, has been reported to occasionally co-bloom with K. brevis but has received little attention as a possible toxin producing species. Therefore, our aim was to investigate the toxin profile for K. papilionacea . A toxic fraction was identified using a cell based cytotoxicity assay and the toxin was isolated and identified as the ladder frame polyether brevetoxin-2 (PbTx-2) using mass spectrometry (MS) and nuclear magnetic resonance (NMR). Toxin production in K. papilionacea increased in response to hypoosmotic stress, as previously observed in K. brevis . Highlights: We found that Karenia papilionacea can no longer be described as a non-toxic dinoflagellate. We found that K. papilionacea produces a brevetoxin, PbTx-2. K. papilionacea produces PbTx-2 at the femtogram concentration as opposed to the nanogram concentration of Karenia brevis . K. papilionacea blooms in the Delaware Bay should be monitored to prevent human exposure to Neurologic Shellfish Poisoning. Toxin production in K. papilionacea increased in response to hypoosmotic stress, as previously observed in K. brevis .